Transference of Ethnic Difference in School - Aldea Muñoz, Serafín (Education Policy Analysis Archives, 2001)
This article attempts to compile those concepts relating to the duality equality—difference, which appears with increasing frequency in our schools. Respect for ethnic minorities, integration, and the need to affirm certain values are part of the rights of children and of all persons. Nevertheless, this work provides evidence of the gap between theory and reality in the classroom. We also examine the difficulty of reaching an agreement as to what should be understood as tolerance or equality, which must be translated into didactic practice through behaviors and actions which go beyond the typical educational treatment or mere information about this worldwide problem.